Pelayanan Hak Tanggungan Elektronik Pasca Terbitnya Permen ATR/BPN Nomor 5 Tahun 2020 Pada Kantor Pertanahan Kota Yogyakarta - Wiyandari, Nur (Officium Notarium, 2024)
Restructuring digitization of land offices is a demand in the development of digital transformation which has consequences related to the authority and responsibilities of the ATR/BPN ministry to respond to challenges in the field of information technology, one of which is the implementation of mortgage rights electronically. Therefore, an interest arose for the author to conduct research with a focus on, among other things: first, Electronic Mortgage Services after the entry into force of the ATR/BPN Ministerial Regulation Number 5 of 2020 Concerning Electronic Integrated Mortgage Services at the Yogyakarta City Land Office has been carried out according to the rules, second, what are the obstacles encountered by the Yogyakarta City Land Office and the solutions to these obstacles. The results of this study were: first, the implementation of HT-el at the Yogyakarta City Land Office by the Regulation of the Minister of ATR/Head of BPN Number 5 of 2020. Starting from work validating data, and ending verifying files. Second, the obstacle faced by the Yogyakarta City Land Office are from the PPAT, bank, and the Yogyakarta City Land Office. What often happens is a problem with a server error, then if the Mortgage can sometimes exceed the allotted time, the fee that has been paid to the Land Office cannot be returned. However, with the issuance of this Ministerial Regulation, in the event of an emergency (force majeure), the money that has been paid can be returned.